The incidence rate and histological characteristics of intimal hyperplasia in elastase‐induced experimental abdominal aortic aneurysms in mice - Meng Li; Panpan Wei; Kexin Li; Haole Liu; Naqash Alam; Haiwen Hou; Jie Deng; Baohui Xu; Enqi Liu; Sihai Zhao; Yankui Li (Animal Models and Experimental Medicine, 2024)
Abstract Intimal hyperplasia (IH) is a negative vascular remodeling after arterial injury. IH occasionally occurs in elastase‐induced abdominal aortic aneurysm (AAA) mouse models. This study aims to clarify the incidence and histological characteristics of IH in aneurysmal mice. A retrospective study was conducted by including 42 male elastase‐induced mouse AAA models. The IH incidence, aortic diameters with or without IH, and hyperplasia lesional features of mice were analyzed. Among 42 elastase‐induced AAA mouse models, 10 mice developed mild IH (24%) and severe IH was found in only 2 mice (5%). The outer diameters of the AAA segments in mice with and without IH did not show significant difference. Both mild and severe IH lesions show strong smooth muscle cell positive staining, but endothelial cells were occasionally observed in severe IH lesions. There was obvious macrophage infiltration in the IH lesions of the AAA mouse models, especially in mice with severe IH. However, only a lower numbers of T cells and B cells were found in the IH lesion. Local cell‐secreted matrix metalloproteinases (MMP) 2 was highly expressed in all IH lesions, but MMP9 was only overexpressed in severe lesions. In conclusion, this study is the first to demonstrate the occurrence of aneurysmal IH and its histological characteristics in an elastase‐induced mouse AAA model. This will help researchers better understand this model, and optimize it for use in AAA‐related research.